Implementasi Algoritma Sequential Searching Pada Sistem Penyedia Informasi Magang Berbayar - Nihdatul Himmah; Jeffri Alfa Razaq (Elkom : Jurnal Elektronika dan Komputer, 2023)
Media information related to the internship is still difficult to obtain, making it difficult for students and students to search for internships. Information about apprenticeships is sometimes incomplete in providing the required requirements as well as unclear registration methods. Sometimes there are students and students who don't have a place for paid internships according to their expertise and so far. This study aims to build a system that can be utilized to provide convenience for students and students in finding information on paid internships and searching data using sequential searching methods. The sequential searching method is used to search for the status of paid internship applications whether accepted or rejected based on the internship application number. The sequential searching method in this study was used to search for the status of paid internship applications whether accepted or rejected based on the internship application number. From the results of testing the data search as much as 15 times out of 350 data using the sequential searching method, the average value of the search time is 15.336 ms, the fastest search process is 10.982 ms and the longest search process is 19.634 ms.